American Torture from the Philippines to Iraq: A Recurring Nightmare. By William L. d’Ambruoso. New York: Oxford University Press, 2021. 224p. 74.00 cloth. - Heaphy, Janina (2023)

British counterterrorism, the international prohibition of torture, and the multiple streams framework - Heaphy, Janina (Policy and Politics, 2022)
After years of violating the basic principles of human rights in the name of counterterrorism, western democracies have begun to implement extraterritorial safeguards that extend protections under the Convention against Torture to foreigners abroad. The case of the UK and the development of the ‘Principles’ in 2019, however, presents a particular puzzle to policymaking research, as it challenges traditional hypotheses regarding the opening of problem windows within the multiple streams framework. Accordingly, the UK presents an interesting case in which a powerful state willingly engaged in self-restraint, despite little electoral pressure to do so and a persistently high terrorist threat. Drawing on theory-building process-tracing, this article addresses this gap using data from semi-structured interviews with British policy experts to present a refined hypothesis, which can also be applied to policy fields of little public interest and processes of foreign policymaking
Created from Fastlane, Scopus look-up
Keywords: Convention against torture; Counterterrorism; Foreign policy; Human rights; Multiple streams framework; Uk

Seeing reason or seeing costs? The United States, counterterrorism, and the human rights of foreigners - Heupel, Monika; Heaphy, Caiden; Heaphy, Janina (European Journal of International Relations, 2022)
It is well known that in the wake of 9/11, the United States committed various extraterritorial human rights violations, that is, human rights violations against foreigners outside of its territory. What is less known is that the United States has gradually introduced safeguards that are, at least on paper, meant to prevent its counter-terrorism policies from causing harm to foreigners abroad or, at least, to mitigate such harm. Based on three case studies on the development of safeguards related to torture, targeted killing, and mass surveillance, we show that two mechanisms, coercion and strategic learning, deployed either on their own or in combination, can account for the development of such safeguards. By contrast, we found no evidence of a third mechanism, moral persuasion, having any direct effect. In other words, US policymakers opt to introduce such safeguards either when they face pressure from other states, courts, or civil society that makes immediate action necessary or when they anticipate that not introducing them will, at a later date, result in prohibitively high costs. We did not find evidence of US policymakers establishing safeguards because they deemed them morally appropriate. From this we conclude that, although the emerging norm that states have extraterritorial (and not just domestic) human rights obligations may not have been internalized by key US policymakers, it nevertheless has a regulative effect on them insofar as the fact that relevant others believe in the norm restricts their leeway and influences their cost–benefit calculations.
Created from Fastlane, Scopus look-up
Keywords: Deterritorialization; human rights; International Relations; national security; norms; War on Terror

US Counterterrorism and the Human Rights of Foreigners Abroad: Putting the Gloves Back On? - Heupel, Monika; Heaphy, Caiden; Heaphy, Janina (Taylor and Francis, 2022)
This book examines why the United States has introduced safeguards that are designed to prevent their counterterrorism policies from causing harm to non-US citizens beyond US territory. It investigates what made US policymakers take steps to “put the gloves back on” through five case studies on the emergence of such safeguards related to the right not to be tortured, the right not to be arbitrarily detained, the right to life (in connection with targeted killing operations), the right to seek asylum (in connection with refugee resettlement), and the right to privacy (in connection with foreign mass surveillance). The book exposes two mechanisms - coercion and strategic learning - which explain why the United States has introduced what the authors refer to as “extraterritorial human rights safeguards”, thus demonstrating that the emerging norm that states have human rights obligations towards foreigners beyond their borders constrains policy choices. This book will be of key interest to scholars and students of human rights, counterterrorism, US foreign policy, human rights law, and more broadly to political science and international relations. The Open Access version of this book, available at: https://www.taylorfrancis.com, has been made available under a Creative Commons Attribution-Non Commercial-No Derivatives 4.0 license.
Created from Fastlane, Scopus look-up

When identity meets strategy: The development of British and German anti-torture policies since 9/11 - Heaphy, Janina (Cooperation and Conflict, 2023)
Since 9/11, considerable research has been done on US interrogation and detention operations, but comparatively little is known about the involvement of other traditionally liberal states’ intelligence agencies and their evolving perspectives on torture-related policies for foreigners abroad. Particularly, the United Kingdom and Germany provide interesting cases; despite similar levels of public and political pressure regarding their indirect involvement in Central Intelligence Agency’s operations, the two states took different strategic decisions in 2010 on whether to implement new extraterritorial human rights safeguards. While the United Kingdom introduced a new intelligence guidance for interrogations overseas, the German government opted for policy-continuance, which raises the question why the two states embarked on different policy trajectories, even if they found themselves in contextually similar situations and were subjected to the comparable accountability measures. By bridging insights from Rationalist and normative literature, the article addresses this conundrum by clearly outlining the states’ differing strategic preferences, and by dissecting the multi-layered composition of these interests. As a result, the article delineates how strategic constraints pertaining to the states’ national, international, or political elite level affect decision-makers’ policy responses.
Created from Fastlane, Scopus look-up
Keywords: convention against torture; counterterrorism; foreign policy; Germany; human rights; identity; rational-choice; UK